Infrared spectroelectrochemical study of dissociation and oxidation of methanol at a palladium electrode in alkaline solution - Yang, Yao-Yue (Langmuir : the ACS journal of surfaces and colloids, 2013)
The dissociative adsorption and electrooxidation of CH(3)OH at a Pd electrode in alkaline solution are investigated by using in situ infrared spectroscopy with both internal and external reflection modes. The former (ATR-SEIRAS) has a higher sensitivity of detecting surface species, and the latter (IRAS) can easily detect dissolved species trapped in a thin-layer-structured electrolyte. Real-time ATR-SEIRAS measurement indicates that CH(3)OH dissociates to CO(ad) species at a Pd electrode accompanied by a "dip" at open circuit potential, whereas deuterium-replaced CH(3)OH doesn't, suggesting that the breaking of the C-H bond is the rate-limiting step for the dissociative adsorption of CH(3)OH. Potential-dependent ATR-SEIRAS and IRAS measurements indicate that CH(3)OH is electrooxidized to formate and/or (bi)carbonate, the relative concentrations of which depend on the potential applied. Specifically, at potentials negative of ca. -0.15 V (vs Ag/AgCl), formate is the predominant product and (bi)carbonate (or CO(2) in the thin-layer structure of IRAS) is more favorable at potentials from -0.15 to 0.10 V. Further oxidation of the CO(ad) intermediate species arising from CH(3)OH dissociation is involved in forming (bi)carbonate at potentials above -0.15 V. Although the partial transformation from interfacial formate to (bi)carbonate may be justified, no bridge-bonded formate species can be detected over the potential range under investigation